Fabrication and characterization of spearmint oil loaded nanoemulsions as cytotoxic agents against oral cancer cell - Sukannika Tubtimsri; Chutima Limmatvapirat; Siripan Limsirichaikul; Prasert Akkaramongkolporn; Yutaka Inoue; Sontaya Limmatvapirat (Elsevier, 2018)
Spearmint oil (SMO), a commonly used essential oil for oral care products, possesses various interesting functions, especially for anticancer property. However, the application of SMO for cancer treatment is limited due to water insoluble. In the present study, nanoemulsions, which have been widely accepted as dosage forms for poorly water-soluble drugs, were selected as candidate carriers for SMO to inhibit oral cancer cell. The nanoemulsions were fabricated using phase inversion temperature method. The factors affecting formation and properties of nanoemulsions including type and amount of surfactants, oil loading and ratio of SMO to virgin coconut oil (VCO) were investigated. Among the surfactants used, the nanoemulsions containing polyoxyethylene castor oil derivatives (Kolliphor®EL; PCO35, Cremophor®RH40; PCO40, Eumulgin®CO60; PCO60) and polyoxyethylene sorbitan fatty acid esters (PSF80) showed 100% creaming after temperature cycling test indicating excellent physical stability while those containing PCO40 demonstrated more transparency and better physical stability. With an increasing amount of PCO40, the droplet size tended to decrease and was in the nano-size range (<1000 nm) after increasing to more than 5% (w/w). SMO-VCO loading also influenced on the droplet size. At 5% (w/w) PCO40, the maximum SMO-VCO loading of 25% (w/w) to attain nanoemulsions was observed. Moreover, the composition of oils had an impact on size of emulsions. The transparent nanoemulsions were only prepared in the range of SMO-VCO from 40:60 to 80:20, suggesting the optimum ratio of SMO to surfactant and the composition of oils were the critical factors for formation of nanoemulsions. NMR study disclosed that the interaction between PCO40 with both VCO and SMO should be a possible stabilization mechanism. Furthermore, the SMO-VCO nanoemulsions exhibited significant cytotoxic effect against oral carcinoma (KON) cell line using MTT assay. The finding, therefore, revealed the good feasibility of SMO-VCO nanoemulsions as novel carriers for treating of oral cancer. Keywords: Nanoemulsions, Spearmint oil, Coconut oil, Surfactants, Anticancer, NMR